The effectivity of clinicians' flossing instructions to oral-med patients in U.P. College of Dentistry - Paras, Ma. Charissa A.; Samsel, Gina D.; Reyes, Benjamin (Adviser).
Flossing has always been considered an important part of Oral Hygiene Instructions in attaining total plaque control. This study aimed to determine how effective the U.P. College of Dentistry clinicians were in giving flossing instructions to their patients. Questionnaires on the knowledge and use of the dental floss were given to all the patients of 26 clinicians of Oral Medicine Section during the first sitting appointment and on the recall appointment. The survey forms given on both time periods contain the same set of questions, with two additional questions on the recall form . This is to determine if there are significant differences in the responses. In addition, the respondents were requested to demonstrate the method of flossing intraorally in the presence of the authors. Data revealed that out of 55 respondents, only 70.91 % are already knowledgeable about flossing and 50.91 % actually use dental floss before the first sitting appointment. Only 6.25 % learned about the concept and importance of the dental floss from the clinicians, while 3.63 % learned its usage after the first sitting appointment. Flossing demonstrations revealed that 42.86 % learned the proper flossing method from the clinicians. The results underline that there is a need for U.P. College of Dentistry clinicians to give more emphasis on the importance and use of the dental floss in providing Oral Hygiene Instructions to their patients.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.